Kerinduan terhadap Tanah Air pada Puisi "Khamsu Ras??ila Il? Umm?" dalam Antologi Puisi Ar-Rasmu Bil-Kalim?t Karya Niz?r Qabb?niy - Evayatun Ni'mah (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This research is aim to tell the meaning of one of a poetry written by a famous poet from Syria under the title Khamsu Ras??ila Il? Umm?. The poem is telling about the deepest feeling of a longing to the lovely homeland. A man who did a long journey to foreign countries due to several conditions needs to recall the memory about his homeland. His homeland he called ‘umm?’ (mother) never leave his heart even he is out of his homeland as his own mother. The poetry has analyzed with semiotic theory that used to know the meaning of meaning of a poetry. There are three stages to analyze this poetry in this research, the first is to search semantic indirection that used by the poet. Semantic indirection is caused by three things, they are displacing of meaning, distorting of meaning, and creating of meaning. After finding the semantic indirection, then doing a semiotic reading that consisting of heuristic reading that as its first level reading and hermeneutic reading as an interpretation by considering the semantic indirection. The last stage is to determine the matrix or keyword of this poetry. The result of this research reflects an expression of a man who had a deep feeling of longing to his homeland when he did live abroad.